(untitled) (Journal of the College of Education for Women, 2019)
Differences in transversal sections and activities of geomorphological operations led to forming geomorphological shapes as river turns and river isles in watercourse in the area of study. The study showed three river turns that are Sindia turn with length 4723m, turn wave 3599 average width 267.6, Zanbour turn length 11374m, turn wave 7110 average width 307.5m,and Dojama turn with length 5876m, turn wave 4982m average width 313.4m. This difference is caused by the activity of erosion and sedimentation that led to the appearance of the length rivers turn.The study showed that the turn of Dojama is the only corresponding turn, whereas the phenomena of corresponding never appeared in other turns in the area of study. The study also showed seven river isles in watercourse differing in aspects, dimensions, and shapes which length rates between 518-2383m with a curve 12.75-27.0; also, it showed that all these isles are permanent.Keywords: Tigris River, Geomorphological Phenomena